Effect of Insulin Therapy in Type-2 Diabetes in Improving Â-Cell Function and Glycemic Control Compared with Oral Anti- Diabetic Agents with or without Insulin in Routine Clinical Practice - R, Bakyaraj; NN, , Rajendran; MP, Narmadha (Indian Journal of Pharmacy Practice)
Observational studies are valuable tools for assessing the applicability of results from randomized controlled trials to broader patient populations. They are especially important in chronic diseases such as diabetes, as they can provide a comprehensive picture of the safety and effectiveness of a particular therapy across cultures and phenotypes.The aim of this study is to determine Efficacy, Safety and Tolerability of the early intervention of insulin treatment with or without Oral Anti Diabetic's (OAD) in type 2 diabetes for improving glycemic control compared with OAD's alone and to determine the persistence of effect up to 6 months in the intervention group in routine clinical practice. The effect of the anti-diabetic agents will be measured by monitoring the Fasting blood glucose level (FBG), Post prandial blood glucose level (PPBG), Glycated hemoglobin levels, C-Peptide levels and all other necessary parameters needed for diabetic management.
Keywords: Type 2 Diabetes; Oral Anti Diabetics; Fasting Blood Glucose Level